Global politics in a changing world - Mansbach, Richard W.; Rhodes, Edward (Bostorn, 2006)
This unique reader goes beyond the traditional concept of International Relations as focused only on interactions between states. It addresses all the players in the current global political scene, from international companies and intergovernmental organisations to traditional states and terrorist organisations. Mansbach/Rhodes blend conceptual writings on International Relations with current events coverage from journalistic sources. Case materials are drawn from all major geographic regions in order to emphasise the global nature of these issues in the post-Cold War period. Each chapter approaches the key topics first from a scholarly/theoretical view, then follows with readings presenting a news/current events context. The readings provide a stimulus for informed debate and discussion and they encourage students to view daily events as part of a larger process of change.
Keywords: Globalization